Using Employment Data From a Medical University to Examine the Current Occupation Situation of Master's Graduates in Public Health and Preventive Medicine in China - Li, Huangyuan; Zheng, Fuli; Zhang, Jie; Guo, Zhenkun; Yang, Hua; Ren, Caixia; Zhang, Wenchang; Wu, Siying (Frontiers in Public Health, 2020)
Aims: The purposes of this study are (1) to understand the current employment situation of master graduates majoring Public Health and Preventive Medicine (PHPM) and (2) to provide evidence for career guidance and training of PHPM competent personnel. Methods: The masters graduated from year 2014-2018 in the School of Public Health were chosen as research objects majoring PHPM. Questionnaires were distributed and answers were collected. The employment situation and characteristics were analyzed based on questionnaire data. Results: The employment rate of these graduates were 95.45%, with them mainly in hospitals, followed by colleges and centers for disease control and prevention. The first paid salaries were merely ordinary. Moreover, the rates of jobs barely or not matching their specialties were 23.64% or 6.36%, respectively. Nevertheless, the percentage of students who stuck with their jobs since graduation remained 82.73%. 40% of the graduates were neutral or dissatisfied with their employments. Furthermore, 29% of them claimed that they were undervalued by the employer. Last but not least, graduates are encouraged to equip themselves with creativity, organizing and management, social networking, interpersonal and professional skills. Conclusion: In overall, the employment status of master graduates of PHPM is in good condition. But problems such as low first paid salaries, jobs not matching specialties and undervalued are observed. It is necessary to improve the employment outcome by reforming training models, formulating employment policies and training efforts.